Dossier’s Presentation: Water Risk: Between Hope and Scarcity - Martínez Moscoso, Andres; Piatek, Dariusz (Iuris Dictio, 2025)
According to the Global Risks Report 2025, the second most significant global risk at the territorial level consists of extreme weather events (Elsner, Atkinson & Zahidi, 2025). Looking at the medium term (10 years), five of the top ten risks are associated with environmental factors: beyond extreme weather events, the report highlights biodiversity loss and ecosystem collapse, critical changes in terrestrial systems, natural resource scarcity (including water), and pollution.
Keywords: water law; environmental law; pollution; Scarcity